2011
DOI: 10.1007/s11033-011-1394-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suitable reference genes for quantitative RT-PCR during development and abiotic stress in Panonychus citri (McGregor) (Acari: Tetranychidae)

Abstract: Quantitative real time reverse transcriptase polymerase chain reaction (RT-qPCR) is preferred for gene expression analysis in living organisms. Currently, it is a valuable tool for biological and ecological studies as it provides a relatively straightforward way to assess the relevance of transcriptional regulation under developmental and stress tolerance conditions. However, studies have shown that some commonly used reference genes varied among different experimental treatments, thus, systematic evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 29 publications
1
57
0
1
Order By: Relevance
“…Additionally, when all samples were examined together BestKeeper also ranked GAPDH as the most stable housekeeping gene; however, while the SD of GAPDH, 1.21, was the lowest of all Þve candidate reference genes, it was outside of the suggested threshold. It is difÞcult to identify which is actually the most stably expressed reference gene when examining all developmental stages and tissues based on the BestKeeper analysis, as it has been previously reported that reference gene stability should be based on both the r value and SD value (Takle et al 2007, MarouÞ et al 2010, Niu et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when all samples were examined together BestKeeper also ranked GAPDH as the most stable housekeeping gene; however, while the SD of GAPDH, 1.21, was the lowest of all Þve candidate reference genes, it was outside of the suggested threshold. It is difÞcult to identify which is actually the most stably expressed reference gene when examining all developmental stages and tissues based on the BestKeeper analysis, as it has been previously reported that reference gene stability should be based on both the r value and SD value (Takle et al 2007, MarouÞ et al 2010, Niu et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional housekeeping genes such as ␤-actin and GAPDH have not always been validated in all experimental conditions in arthropods and later gene expression studies have shown that other genes including ␣-tubulin (Bactrocera dorsalis); elongation factor 1-á (EF1␣), RNA polymerase II large subunit, ␣-tubulin, GAPDH (Panonychus citri); and EF1␣ (Rhipicephalus appendiculatus and R. microplus) may be more reliable for use as a reference genes in qRT-PCR analysis (Nijhof et al 2009, Shen et al 2010, Niu et al 2012. Interestingly, Ixodes scapularis (Say) ␤-actin is routinely used in qRT-PCR experiments (Pedra et al 2006, Sukumaran et al 2006, Karim et al 2010, however, an elegant study showed that Anaplasma phagocytophilum induces Actin phosphorylation in I. scapularis .…”
mentioning
confidence: 99%
“…Multiple specific Primers (Table 2) were designed by using Primer Premier 5.0 software (PREMIER Biosoft International, California). The expression study was performed on an Mx3000P TM Multiple Quantitative PCR System (Stratagene, La Jolla, California, USA) with ELF1A, elongation factor-1 alpha, used as reference gene (Niu et al 2012). The reaction system and reaction parameters were same as Niu et al (2012) described earlier.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…The expression study was performed on an Mx3000P TM Multiple Quantitative PCR System (Stratagene, La Jolla, California, USA) with ELF1A, elongation factor-1 alpha, used as reference gene (Niu et al 2012). The reaction system and reaction parameters were same as Niu et al (2012) described earlier. After collecting the Ct values, the relative quantitative expression of these 5 genes were calculated by the 2 -СT method (Livak & Schmittgen 2001).…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…Está envolvida em diversos processos celulares tais como mobilidade celular, contração muscular, citocinese e divisão celular (Niu et al 2012;Lu et al 2013 Helicoverpa armigera (Zhang et al 2014;Shakeel et al, 2015), Nilaparvata lugens (Yuan et al, 2014), Bemisia tabaci , Spodoptora litua (Lu et al, 2013), Frankliniella occidentalis (Zheng et al, 2014) e Sesamia inferens (Sun et al, 2015). , Helicoverpa armigera (Zhang et al, 2014;Shakeel et al, 2015), Sesamia inferens (Sun et al, 2015), Toxoptera citricida (Shang et al, 2015).…”
Section: Discussionunclassified